Modeling Ontology and Semantic Network of Regulations in Customs and Excise - Eva Maulina Aritonang; Kudang Boro Seminar; Sri Wahjuni; Onno Widodo Purbo (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2017)
Regulations in customs and Excise have an important function in regulating legally every policy and decision making. Thus, the type of rules are made varies according to the hierarchy of the regulator. This regulation is also changing, following policy developments that occured in the higgest government. then, what if this organization has not been able to manage its regulatory archiving? even regulatory changes can not be tracked? So, we need a well-organized system that can accomodate all of the rules and the associated changes and connectedness with other type of regulations. This system will help us to provide convenience to users to search, manage and track the history of changes as well as the relationship between the rules used by the organization. This paper propose the design of an ontology-based semantic network using a graph database that use neo4j 2.3.1 as a solution. In the application that uses the sample data, we found 13 types of nodes that contains 242 child nodes and 22 type of relation that contain 548 relation that connect all the node within 3305ms.